Foils in Jane Austen’s Mansfield Park and Anita Brookner’s Providence – A Comparative Study - Janaki, Dr. B. (IJRDO- Journal of Educational Research, 2017)
The main objective of this paper is to spell out the juxtaposition of the two types of women, plain looking yet virtuous and physically attractive yet morally shallow present in Jane Austen‟s Mansfield Park and Anita Brookner‟s Look at Me. Jane Austen (1775-1817), the prominent woman writer of the eighteenth century was a creative artist of great singularity and unique vision. Austen not only limits herself to the sphere she understands, she even picks and chooses amongst the raw material of experience available to her, „3 or 4 Families in a Country Village is the very thing to work on,‟1 and develops the themes of the novels that are significant for the moral concern, perplexity and commitment.